UNIVERSAL BASIC EDUCATION ADMINISTRATION IN NIGERIA: EMERGING ISSUES AND CHALLENGES AND THE WAY FORWARD - Elenwo, Pritta Menyechi; Ebom-Jebose, Abigail (International Journal of Educational Excellence and Innovation, 2024)
This paper conducted a study on the Universal Basic Education administration in Nigeria, with a specific focus one merging issues and challenges and the way forward. Universal basic education in Nigeria faces significant challenges and emerging issues in its administration. The primary objective was to address the inception of Universal Basic Education (UBE), its objectives and identifying the issues and challenges of UBE programme, which aimed to provide free, high-quality education for children between the ages of 6 and 15 and suggest the way forward. The paper highlighted that the administration of Universal Basic Education is hindered by myriads of issues and challenges such as,poor planning, financing and sustainability, lack of quality teachers, education infrastructure, monitoring and evaluation, parental and community involvement, technology integration, and inclusive education.The paper emphasized the importance of combating these issues and challenges for effective administration to ensure the success of UBE. In conclusion, by implementing these measures, Nigeria can ensure that all children have access to quality education, thereby promoting their overall development and contributing to the country’s economic growth and development.To address these challenges, the researchers suggested among others that,a clear and comprehensive plan should be developed for UBE implementation, outlining specific objectives, strategies, and timelines, the allocation of funds for UBE should be increased, and the funds should be utilized effectively to ensure the program’s success, efforts should be made to recruit and train quality teachers, providing them with the necessary resources and support to deliver quality education and efforts should be made to provide basic facilities in schools, including classrooms, toilets, and water.